Kajang by-election: a study of voter behaviour - Syed Abdullah Idid, Syed Arabi; Souket, Rizwanah; Wakichan, Azrul Hisyam (2019)
This paper evaluates the Kajang by-election held in 2014 from the perspective of the third person effect. The state seat of Kajang was considered important given the poor results obtained by the ruling party, Barisan Nasional, then, a party that lost for the second successive time its two-third parliamentary strength. The Kajang by-election was held where PKR president Wan Azizah Wan Ismail was challenged by Chew Mei Fun, a Malaysian Chinese Association (MCA) vice president, representing the BN. This by-election was significant as it was held after the recent general elections and was a good ground to test the voter’s state of mind and perception towards the ruling party. The Kajang by-election resulted in PKR (People's Justice Party) winning with a victory margin of 19% garnering a greater Malay support. This study was conducted to test the impact of the political campaign messages on the voters. Voter perception was studied and analyzed from phase one that was done from 1 to 8 March and phase two that was done from 29 to 31 March. Based on the analysis of survey responses from the sample (phase one, n = 589 and phase two, n = 619), we found not much differences in the voter behaviour between phase one and phase two, thus confirming their choice of party. Comparisons on the voter behaviour in both phases were made in the context of gender, race, age, education level and income. The survey study also retrospectively tested for the presence of a third-person effect, aiming to investigate the perceived self-other discrepancy with regard to how the political campaign messages influenced voters’ choice of party. Results indicated a reverse third person effect on the recipients of favourable party messages thus affecting their decision making.